A novel approach to monitor skin permeation of metals in vitro - Midander, Klara; Schenk, Linda; Julander, Anneli (Regulatory toxicology and pharmacology, 2020)
How metals permeate skin is poorly understood. Risk assessments tend to take default approaches to account for the dermal route, often using numbers of questionable relevance. Moreover, simultaneous exposure to multiple metals may affect the permeation of individual metals. To investigate this, we developed an experimental setup where receptor medium circulates directly from a conventional diffusion cell for in vitro skin absorption into an inductively coupled plasma mass spectrometer (ICP-MS), enabling continuous measurement of metal concentration. Full-thickness piglet skin was used as diffusion barrier, artificial sweat as donor medium and phosphate buffered saline as receptor medium. Percutaneous absorption from donor medium containing 2 mmol/L of nickel, cobalt, or chromium or all three combined was monitored for 2 h. Metals retained in skin were quantified post-exposure. Percutaneous absorption of nickel was faster in single than in combined exposure; for cobalt and chromium no such difference was apparent. Similar amounts of the three metals were retained in skin after single exposure, and retention was consistently higher for each metal after combined exposure. This study provides proof-of-concept for a method that reliably detects concentration changes in physiologically relevant medium. It may shed light on skin absorption and permeation kinetics of metals and risks associated with metal exposure. [Display omitted] •A method for measuring skin permeation of several metals during ongoing exposure.•Concentration changes in a physiologically relevant receptor medium were detectable.•Permeation rates and skin retention for single and combined exposures are compared.